Kualitas Pelayanan Bus Trans Jatim Terhadap Kepuasan Masyarakat - Luluk Nafilatur Rizqi; Rachmawati Novaria; Indah Murti (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This study aims to identify and further analyze the service quality of the Trans Jatim Corridor I Bus to achieve public satisfaction. The method used is to use a qualitative approach by describing in accordance with the theory of the five dimensions of service quality from Zeithaml et. al. (1990) namely tangible, reliability, responsiveness, assurance, and empathy. Data were collected using interviews, observation, and documentation methods. The results of this study indicate that the quality of Trans Jatim Bus services on the Corridor I route is good and provides satisfaction to the community. This is evidenced by the fulfillment of the components in the five dimensions of service quality, namely the facilities are quite good, the reliability and ability of the officers are good, the good response given by the officers when responding to problems, the officers are also polite and friendly, and the guarantees provided are also good (such as legality, on time, and cost certainty). However, there is still a need for innovation and improvement regarding the services provided in order to continue to provide optimal and quality services. Such as uneven service facilities provided, in terms of discipline officers are less consistent, and often the response or response given by officers exceeds the provisions (1 x 24 hours).